Amazon dieback beyond the 21st century under high-emission scenarios by Earth System models - Irina Melnikova; Tomohiro Hajima; Hideo Shiogama; Michiya Hayashi; Akihiko Ito; Kazuya Nishina; Kaoru Tachiiri; Tokuta Yokohata (Communications Earth & Environment)
Abstract The Amazon rainforest, the world’s largest tropical forest, plays a crucial role in climate regulation but faces risks of dieback under climate change. Here, we examine the Amazon dieback projections from state-of-the-art Earth System Models under high-emission scenarios extending into the 23rd century. Unlike previous studies focused on rapid changes, we investigate both rapid and gradual dieback, capturing drastic productivity declines (>80%). Nine of twelve models project Amazon dieback with variations in timing and spatial extent. The dieback onset is projected within the 21st century under global warming levels ranging from 1.5 to 10.2 °C, triggered by local surface air temperatures above 32.2 ± 4.8 °C and precipitation below 1394.3 ± 306.0 mm year−1, exacerbated by land-use change. We identify large-scale atmospheric circulation changes causing regional drying and warming and examine ecosystem processes contributing to dieback. These findings refine our understanding of Amazon dieback thresholds and mechanisms, highlighting areas for model improvement.